2020
DOI: 10.1155/2020/9106390
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Significant Response to Olaparib in a Patient with Primary Peritoneal Carcinosarcoma Diagnosed by Laparoscopic Surgery

Abstract: Primary peritoneal carcinosarcomas which arise from extragenital locations are extremely rare. Carinosarcomas contain both carcinomatous and sarcomatous elements and can be mainly detected in the female genital tract. We herein report a case of primary peritoneal carcinosarcoma diagnosed by laparoscopic surgery and treated with olaparib. A 62-year-old woman referred to our hospital due to abdominal distension. From imaging findings, we suspected advanced primary peritoneal carcinoma, and laparoscopic surgery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Olaparib therapy for PPCS has not yet been reported. Nagamata et al [ 30 ] reported a significant response to olaparib in a patient with a PPCS, although neither germline nor somatic genetic testing was performed to assess BRCA status. In the present case, the patient had a BRCA germline pathogenic variant, but the mutational signature was discordant.…”
Section: Discussionmentioning
confidence: 99%
“…Olaparib therapy for PPCS has not yet been reported. Nagamata et al [ 30 ] reported a significant response to olaparib in a patient with a PPCS, although neither germline nor somatic genetic testing was performed to assess BRCA status. In the present case, the patient had a BRCA germline pathogenic variant, but the mutational signature was discordant.…”
Section: Discussionmentioning
confidence: 99%
“…There is another published case report of olaparib maintenance therapy in OCS, but in that case, the patient was BRCA non-mutated. The patient was administered olaparib for recurrent platinum-sensitive disease, with a progression after seven months of therapy [ 14 ]. By comparison, our patient had a better outcome, so the presence of biomarkers ( BRCA mutation) could help to identify the population that would most benefit from this strategy.…”
Section: Discussionmentioning
confidence: 99%